Multiple endocrinopathies acquired using a checkpoint inhibitor - Pembrolizumab: A Case Report - Marcelino, Gustavo César Sola Barreto; Miranda, Eduarda Lavínia Mota de; Sebastianes, Fernando (Brazilian Journal of Case Reports, 2024)
Immunotherapy with checkpoint inhibitors (ICIs) has been increasingly employed for the treatment of many malignancies, and endocrinopathies are one of their most frequent side effects. This case report describes a 70-year-old man who faced many endocrinopathies (primary hypothyroidism, secondary adrenal insufficiency, and diabetes mellitus) after initiation of immunotherapy with an ICI (pembrolizumab) for treatment of urothelial bladder cancer. We discuss the prevalence, physiopathology, screening, and diagnosis of each of these abnormalities. Clinicians need to be aware of these endocrine complications of ICI therapy and be ready for early diagnosis and appropriate management.